Homogenizing coordinates through the use of the active CORS1 in Ghana - Abukari, Osman Mohammed; Acheampong, Akwasi Afrifa; Osah, Samuel; Ayeh, John (South African Journal of Geomatics, 2024)
This is an article published in South African Journal of Geomatics, Vol. 12. No. 2, August 2023 ; http://dx.doi.org/10.4314/sajg.v12i.2.2